La Châtelaine de Vergy comme histoire tragique matrimoniale : de Marguerite de Navarre (1558) à Bandello (1573) et Le sixiesme tome des histoires tragiques (1582) - Leushuis, Reinier (Renaissance and Reformation / Renaissance et Réforme, 2009)
The anonymous thirteenth-century poem La Châtelaine de Vergy, a courtly love story that ends in bloodshed after its central secret is divulged, was adapted as the 70th novella in Marguerite de Navarre’s Heptaméron (published 1558–1559). Matteo Bandello’s Italian adaptation of this version of the story (in his posthumously published Quarta parte delle novelle [1573]) introduces an important change by specifying that the lovers are now clandestinely married; this detail is retained in an anonymous French translation of Bandello’s reworking, which appeared in one of the volumes of the popular Histoires tragiques. While critics have been puzzled at this apparent narrative flaw (marriage needs no secrecy), this essay argues that the shift is intentional by considering it in light of the problem of clandestine marriages and post-Tridentine matrimonial reform. While Marguerite’s novella already recasts the Châtelaine de Vergy story in matrimonial terms, Bandello further exploits its drama of speech, in which tragic events are triggered through speaking and divulging secrets, to question the Church tradition of contracting matrimony merely by the partners’ spoken words. A number of textual ambiguities in the French translation reveal furthermore that the story has subsequently been re-interpreted from a new perspective on betrothal as a non-binding spoken promise that gained ground during the Counter-Reformation. The textual transformations introduced into these three versions, moreover, are examined in the context of the development of the “histoire tragique” as a literary genre during the second half of the sixteenth century. This study thus identifies a correlation between the characteristics of the “histoire tragique” and matrimony’s socio-historical dynamics.